GROWTH COMPARISON DAN SURVIVAL RATE OF CATFISH (Clarias sp.) WITH DIFFERENT FEED - N. P. P, WIJAYANTI; PEBRIANI, D. A. A. (Majalah Ilmiah Peternakan, 2021)
This study aims to determine how the growth and survival of catfish seeds that are fed differently. The design used was a completely randomized design (CRD) using 4 treatments and 3 replications so that the number of expe- riments amounted to 12. The treatment given was treatment A (administration of daphnia magna), treatment B (administration of tubifex), treatment C (mosquito larvae), and treatment D (pellets). The parameters measured in this study are weight growth, feed conversion ratio (FCR), survival rate (SR), and water quality parameters (acidity (pH), temperature, and dissolved oxygen (DO). Research location was carried out at the UPT. Fish Seed Market and Fish Seed Center Denpasar City. The highest weight growth was in treatment B was 0.89 g, then in treatment D was 0.84 g, treatment C was 0.42 g, and treatment A was 0.37 g. The best FCR in treatment B was 1.90 and treatment D was 1.98. Survival rate in this study ranged from 70-90%. Water quality parameters in this study are still in good conditions for growth and survival of catfish seeds. The temperature ranges from 24.97-25.10oC, DO ranges from 4.63-8.02 ppm, and pH ranges from 8.97-9.23.